2016
DOI: 10.1074/jbc.m115.710087
|View full text |Cite
|
Sign up to set email alerts
|

Different Epidermal Growth Factor Receptor (EGFR) Agonists Produce Unique Signatures for the Recruitment of Downstream Signaling Proteins

Abstract: The EGF receptor can bind seven different agonist ligands.Although each agonist appears to stimulate the same suite of downstream signaling proteins, different agonists are capable of inducing distinct responses in the same cell. To determine the basis for these differences, we used luciferase fragment complementation imaging to monitor the recruitment of Cbl, CrkL, Gab1, Grb2, PI3K, p52 Shc, p66 Shc, and Shp2 to the EGF receptor when stimulated by the seven EGF receptor ligands. Recruitment of all eight prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 43 publications
(14 reference statements)
3
54
0
1
Order By: Relevance
“…The sustained nature of the autophosphorylation signal at any ligand concentration suggests that it is indeed a feature of the EREG/EGFR or EPGN/EGFR complex rather than a consequence of low ligand affinity or receptor occupancy. Importantly, we also showed that amphiregulin promotes transient EGFR autophosphorylation (Figure S6D) despite binding the receptor with a similar (or lower) affinity than epiregulin or epigen (Ronan et al, 2016; Wilson et al, 2012). This is consistent with the ability of amphiregulin to induce sEGFR501 dimerization (Figure 4A), and further argues that reduced dimerization and sustained receptor activation are not simply consequences of low ligand/receptor affinity.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The sustained nature of the autophosphorylation signal at any ligand concentration suggests that it is indeed a feature of the EREG/EGFR or EPGN/EGFR complex rather than a consequence of low ligand affinity or receptor occupancy. Importantly, we also showed that amphiregulin promotes transient EGFR autophosphorylation (Figure S6D) despite binding the receptor with a similar (or lower) affinity than epiregulin or epigen (Ronan et al, 2016; Wilson et al, 2012). This is consistent with the ability of amphiregulin to induce sEGFR501 dimerization (Figure 4A), and further argues that reduced dimerization and sustained receptor activation are not simply consequences of low ligand/receptor affinity.…”
Section: Resultsmentioning
confidence: 68%
“…Numerous studies report distinct EGFR-dependent cellular responses to the different ligands (Wilson et al, 2009), with a given cell line responding differently to individual EGFR ligands in terms of cell proliferation (Wilson et al, 2012), differentiation (Kochupurakkal et al, 2005; Rizzi et al, 2013), and/or motility (Willmarth and Ethier, 2006). Individual EGFR ligands also induce qualitatively and quantitatively different downstream signals (Knudsen et al, 2014; Ronan et al, 2016; Wilson et al, 2012), and are linked to unique phenotypes in vivo (Wilson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, most of the nodes in the signaling pathway followed the same direction in Estradiol, ICI 5 lg or ICI 5 mg groups compared with the control group. The direction of the genes corresponding to factors found within the cytoplasm could vary relative to the dynamics of the responses to the different ligands since it has been shown that recruitment of the downstream signaling proteins differs between EGFR agonists and also between different doses of the same agonist (Ronan et al 2016). However, it is interesting to note that the membrane receptor (EGFR) and one of the most important nuclear ligand-activated transcription factors for estradiol (ESR1) are upregulated in all the treatments, although the difference of expression for these genes between the treated and control fetuses in the general statistical analysis was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of the EGFR signaling pathway is organized around a central repertoire of enzymes and adapter proteins that is capable of producing a large variety of cellular outcomes depending on the cellular context (1,14). The timing and extent of phosphorylation and effector recruitment varies, depending on which ligands and heterodimerization partners are present (60)(61)(62)(63). One explanation for the ability of different EGFR-family ligands to produce alternative phosphorylation and effector recruitment patterns is the intrinsic sequence specificity of EGFRfamily kinases, which can determine which sites become phosphorylated and able to support effector binding at different thresholds of kinase activity.…”
Section: Discussionmentioning
confidence: 99%